Pengaruh Brand Image dan Persepsi Harga terhadap Keputusan Pembelian Produk Thrifting pada Kalangan Mahasiswa - Amrullah, Devaldo Yazid; Isyanto, Puji; Sumarni, Neni (Journal of Business and Economics Research (JBE), 2025)
This study is motivated by an effort to analyze the influence of brand image and low prices on the purchase decision of thrifting products among students in Karawang Regency. Thrifting as an alternative to shopping for clothes at low prices among students. This study applied quantitative methods with a causal approach as well as linear-multiple regression analysis techniques. The sample consisted of 97 students in Karawang Regency who had purchased thrifting products, selected using the lemeshow formula. The findings of the study show that brand image and low prices partially and simultaneously have a positive and significant impact on purchase decisions with an r-square value of 0.884 or 88.4%. Brand image gives confidence in product quality, while affordable prices increase consumer appeal. These results show important implications for thrifting business people in designing effective marketing strategies and for the government to be able to formulate regulations related to the cleanliness of thrifting products.